Representação socioeconômica oitocentista: mobilidade social e aburguesamento sob o olhar (oblíquo) de Machado de Assis (1880-1904) - Pereira, Thais Silva (2021)
The purpose of this work is to understand and recognise the representation made by Machado de Assis of the growing social mobility and “bourgeoisie” that occurred in Brazilian society in the last decades of the 19th century - times of modernizing Project —, as well as observing possible transformations in the oblique and argute look of Cosme Velho Wizard about this process and its agents. Will be contemplated two temporalities, of the narrative and of the author, as well as the influence of each of them on the Machado de Assis representation of the social ascension process of “bourgeois” subjects. To this end, four important novels of Machado de Assis published between the years 1880 and 1904 will be analyzed: “Memoirs Posthumous of Brás Cubas” (1880-1881), “Quincas Borba” (1892 - final version), “Dom Casmurro” (1899) and “Esaú e Jacó” (1904 ). It should be noted that the study under development focuses on the trajectory and diagnosis of social mobility and “bourgeois” profiles, and such books are not appreciated in all their extension and complexity. It should be noted that the focus is on the way in which the author literarily represented social mobility and “bourgeoisie”, mindful of the fact that he himself was the result of relative social ascension and “bourgeoisie”. Machado de Assis was one of the authors who best knew how to portray the social structures of his time and, in his critical representation, the “bourgeois” rise would be accompanied by theft, violence, opportunism and speculation